Trade Related Institutions and Development - Jaime de Melo; Marcelo Olarreaga (Fondation pour les études et recherches sur le développement international (FERDI), 2017)
The paper focuses on the role played by Trade Related Institutions (TRIs) in shaping trade flows and their development impact in low-income countries and how these TRIs are shaped by international trade. Three types of TRIs are examined: i) trade agreements; ii) trade promotion organizations; and iii) private TRIs, i.e. fair trade labelling, trading platforms and reputation mechanisms. Recent research reviewed for each type of TRI is then followed by suggestions for further work.
Keywords: F13; F63; O19; O24; 330; Trade related institutions; Development